Roy digs dirt - Shannon, David, 1959- (The Blue Sky Press, an imprint of Scholastic, Inc., 2020)
Roy is a West Highland terrier who loves to dig in the dirt and mud; sometimes he buries things, and sometimes he finds things, but mostly he just likes to dig--even though he does not like the bath that may follow the digging.